Pengaruh Media Sosial Facebook Terhadap Minat Beli Online Mahasiswa Pendidikan Ekonomi FKIP Universitas Flores Ende - Banda, Yosef Moan; Bupu, Herlina (Ekspektasi: Jurnal Pendidikan Ekonomi, 2024)
This research aims to find out: (1) The influence of Facebook social media in growing students' online buying interest. (2) Student buying interest. This type of research is quantitative. The data collection technique uses (1) observation, ((2) questionnaires and (3) documentation. The data analysis technique is to use statistical data analysis with a simple linear regression formula. The results of this research show that (1) there is a significant influence between the Facebook Social Media variables (X1) regarding interest in buying online among students of the Economic Education Study Program at the University of Flores. The analysis results show that the value of t> t table is 7.198> 2.14479 and the significance level is 0.000 < 0.05.